Development and learning of larvae and adults of Spodoptera frugiperda (Lepidoptera: Noctuidae) reared on different cowpea genotypes - da Silva, Suelen Pires; Costa, Eduardo Neves [UNESP]; Fernandes, Marcos Gino; Martins, Lucas Ortega (Springer Nature, 2025)
Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is a primary pest of cowpea, capable of defoliating the crop throughout its growth period. This study evaluated (i) the development of S. frugiperda from laboratory- or field-derived larvae reared for two generations on four cowpea genotypes (Nioaque, Fradinho, BRS Tumucumaque, and Miranda), and (ii) the effects of habituation, preference induction, and pre-imaginal conditioning on host preference. We tested whether repeated exposure influenced larval feeding on resistant or susceptible genotypes and whether adults preferred to oviposit on the genotype experienced as larvae, respectively. The landrace Nioaque significantly reduced the larval and pupal weights of S. frugiperda. Larvae from Nioaque-reared parents showed partial habituation; they preferred Nioaque leaves over those of the Fradinho and BRS Tumucumaque cultivars. However, no preference was observed when compared with the Miranda cultivar. Preference induction was observed in larvae from moths reared on BRS Tumucumaque and Miranda, as they consistently chose leaves of the cultivar on which their progenitors were reared in both experiments. Pre-imaginal conditioning was only partially observed; although moths preferred ovipositing on the genotypes on which they and their parents were reared compared to two other genotypes, there was no difference in the number of eggs laid on the Miranda cultivar compared to that on the other genotypes. Larval and adult learning might assist pest management through sowing small plots of previously cultivated cowpea to allow targeted control before crop establishment.